Group physiotherapy compared to individual physiotherapy to treat urinary incontinence in aging women: study protocol for a randomized controlled trial - Chantale Dumoulin (Trials, 2017)
Abstract Background Urinary incontinence (UI), one of the most prevalent health concerns confronting women aged over 60 years, affects up to 55% of older community-dwelling women—20–25% with severe symptoms. Clinical practice guidelines recommend individualized pelvic floor muscle training (PFMT) as a first-line treatment for stress or mixed UI in women, although lack of human and financial resources limits delivery of this first-line treatment. Preliminary data suggest that group-based treatments may provide the answer. To date, no adequately powered trials have evaluated the effectiveness or cost-effectiveness of group compared to individual PFMT for UI in older women. Given demographic projections, high prevalence of UI in older women, costly barriers, and group PFMT promising results, there is a clear need to rigorously compare the short- and long-term effectiveness and cost-effectiveness of group vs individual PFMT. Methods/Design The study is designed as a non-inferiority randomized controlled trial, conducted in two facilities (Montreal and Sherbrooke) in the Canadian province of Quebec. Participants include 364 ambulatory, community-dwelling women, aged 60 years and older, with stress or mixed UI. Randomly assigned participants will follow a 12-week PFMT, either in one-on-one sessions or as part of a group, under the supervision of a physiotherapist. Blinded assessments at baseline, immediately post intervention, and at one year will include the seven-day bladder diary, the 24-h pad test, symptoms and quality of life questionnaires, adherence and self-efficacy questionnaire, pelvic floor muscle function, and cost assessments. Primary analysis will test our main hypothesis that group-based treatment is not inferior to individualized treatment with respect to the primary outcome: relative (%) reduction in the number of leakages. Discussion Should this study find that a group-based approach is not less effective than individual PFMT, and more cost-effective, this trial will impact positively continence-care accessibility and warrant a change in clinical practice. Trial registration ClinicalTrials.gov, NCT02039830 . Registered on 12 December 2013; Study protocol version 2; 21 November 2013.